The political is personal: disturbing form, revisiting liberalism and resisting Trump's America in The Good Fight - McNally, Karen (Wayne State University Press, 2022)
This book chapter explores how The Good Fight’s combined approaches to narrative and style emphasize the effect of the contemporary political climate on the individual and its relationship to the increasing personalization of politics. Examining how the show tackles the blurring of boundaries between fact and fiction, the political chaos and lawlessness, and the racial and gender inequalities evident in American culture, the chapter considers how style and form are used to illuminate and critique the unsettling dynamics of America's Trump era.